Profile of preterm newborn hospitalized in intensive care unit of high complexity hospital - Oliveira, Caroline de Sousa; Casagrande, Gabriela Ay; Grecco, Luanda Collange; Golin, Marina Ortega (ABCS Health Sciences, 2015)
Introduction: Epidemiological research consists of foundation for advances in health care. Nationally, studies on characterization of different populations are not common, especially in relation to newborn preterm infants (PTI). Objective: Characterize the newborn preterm infants attended in the Neonatal Intensive Care Unit of the Hospital Estadual Mário Covas in Santo André the delineation of the breast profile, gestational, perinatal and period of hospitalization. Methods: This is a descriptive cross-sectional study. We analyzed 218 medical records of all patients seen by the physiotherapy service from 2008 to 2011 and then bounded to the consecutive sample of 81 of them, which followed the inclusion and exclusion criteria. The data were organized and tabulated with SPSS v.17.0 program. The chi-square test was used to compare the frequency of neonatal complications. Results: The mothers had a mean age of 25.7 years, and 68.6% received prenatal care. The pregnancy complications were observed in 37.3%, with the most common urinary tract infections in 28%. The mean birth weight was 1478.6 g and gestational age of 30.8 weeks. The average length of stay of preterm infants was 36 days. Respiratory disorders occurred in 95.2%, with early respiratory distress the most common (95.2%). PN requiring mechanical ventilation were 97.6% and neurological disorders were less frequent (9.87%). Conclusion: Respiratory complications were common in this population and significantly associated with gestational age less than 32 weeks. Prolonged hospitalization after birth is closely related to low birth weight and gestational age at birth.